(untitled) (Bangladesh Journal of Obstetrics & Gynaecology, 2013)
Objective: To study on clinical profile & maternal - fetal outcome of eclamptic patient. Methods: A prospective cross sectional study was done in the department of Obstetrics & Gynaecology in Chittagong Medical College and Hospital from January to December 2010. All patients with eclampsia were included in the study, it was 416. Patients came with convulsion other than eclampsia e.g. epilepsy, malaria, septicemia, meningitis, encephalitis, cerebral haemorrage, high fever, hepatic coma were excluded. Main outcome measures: Incidence of eclampsia, sociodemographic status, ante natal care, time interval between attack and admission, level of consciousness was assessed by AVPU(Alert, response to voice, response to pain stimuli, Unconsciousness) score, types of eclampsia patients (antepartum,intrapartum,postpartum), number of convulsion, gestational age distribution of the patients, mode of delivery , maternal and fetal outcome. Results: Total number of deliveries during this period was 13,635. The incidence of eclampsia in this study was 3.05 %. Among 416 patients with eclampsia most of the patients were between 20-25 years (77%), a large number were primi para (72.5%), most of them comes from rural area (76%), most of them belongs to poor socioeconomic condition (72%), 49% patients were illiterate, 60 % patients had no antenatal check up, 52 % patients came after 6 hours of beginning of convulsion, 18 patients (4%) were unconscious, most of the patients had antepartum eclampsia (64%) , number of convulsion was between 5-9 in about 58% case , 63% were delivered by LSCS, 23% mother showed complications of eclampsia, of them pulmonary oedema (7.45%) and renal failure(6.49%) were common, 35 (8%) mothers were died. Among perinatal mortality 18% baby were stillbirth and 9% were early neonatal death. Conclusion: Eclampsia is still a major killer disease in Bangladesh. It is a preventable disease if preeclampsia is diagnosed by antenatal care. By giving quality antenatal care, mass awareness regarding the importance of antenatal care, emergency obstetric service in the upazilla health complex we can prevent eclampsia. Female education, employment, empowerment is urgently needed to reduce the incidence of this killer diseases. DOI: http://dx.doi.org/10.3329/bjog.v26i2.13784 Bangladesh J Obstet Gynaecol, 2011; Vol. 26(2) : 77-80